Antimicrobial Activity of Starfruit Leaf Extract Against Gram-Positive and Gram-Negative Bacteria - Pauzan, Pauzan; Kurniawan, Edy; Hafisah, Nurul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Starfruit (Averrhoa bilimbi L.) is a plant traditionally used as medicine, mainly due to its secondary metabolite content that has the potential as an antimicrobial agent. This study aims to evaluate the antimicrobial activity of A. bilimbi leaf extract against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria. Extraction was carried out using three types of solvents: 100% ethanol, 100% ethyl acetate, and a mixture of ethanol-ethyl acetate (1:1) using the maceration method. Antimicrobial activity tests were carried out using the disc diffusion method to measure the inhibition zone of bacterial growth. The results showed that all A. bilimbi leaf extracts had inhibitory activity against both types of test bacteria. The extract with ethyl acetate solvent showed the largest inhibition zone against S. aureus and E. coli, followed by the mixed ethanol-ethyl acetate extract, and then the ethanol extract. These findings indicate that the active compounds in A. bilimbi leaves are more soluble in ethyl acetate and have the potential to be developed as natural antibacterial agents.